Bacterial Profile and Antibiotic Susceptibility Pattern of Bacterial Keratitis at a Tertiary Hospital in Riyadh - Almizel, Abdulrahman (Clin Ophthalmol, 2019)
BACKGROUND: The most common cause of ocular infections worldwide is bacteria; therefore, bacterial keratitis requires rapid and proper intervention because it is a major cause of loss of vision and ocular morbidity. Resistance studies have found increases in the resistance to ciprofloxacin, cefazolin, and gentamicin in bacterial keratitis cases that are caused by gram-positive organisms. AIM: To identify the common predisposing factors, causative organisms, and antibiotic profile of bacterial keratitis (BK) in a tertiary care hospital in Riyadh, Saudi Arabia. METHOD: This is a retrospective study of the microbiological record of all patients diagnosed with BK at KAUH. From the first of May 2015 until the first of January 2018. Demographic data, diabetes mellitus, contact lens use, history of eye trauma, ocular surface disorders, recent ocular surgeries, current and recent medications, initial and final visual acuity, and location and size of the infiltrate were all used in the study. VA was converted to the logarithm of the minimum angle of resolution (LogMAR) for statistical analysis. RESULTS: 177 cases positive for BK were included. 100 (56.5%) were males, and 77 (43.5%) were females. The mean age was 43.15. Trauma was the most common predisposing factor, which was observed in 68 (38.4%) cases, followed by Ocular surface disease [52 (29.4%)]. Staphylococcus epidermidis was the most commonly isolated organism [61 (34.5%)], followed by Streptococcus pneumoniae [23 (13%)], and Staphylococcus aureus [18 (10.2%)]. All gram-positive cases were Vancomycin sensitive. Staphylococcus epidermidis showed only 4 resistant cases to chloramphenicol (7.27%), and resistance to penicillin and ampicillin was found in 55 (90%) and 53 (89.83%) cases, respectively. All Streptococcus pneumoniae cases were resistant to gentamicin (100%). Staphylococcus aureus showed high sensitivity for erythromycin [18 (100%)]. CONCLUSION: The most common cause of bacterial keratitis was Staphylococcus epidermidis (N=61), followed by Streptococcus pneumoniae (N=23). Trauma was the most common predisposing factor (38.4%), while contact lens use was only identified in 14 cases (7.9%). All organisms tested were sensitive to vancomycin, and there was high resistance toward penicillin (90%).